Economic Importance of Air Transport and Airport Activities in Belgium – Report 2009 - Xavier Deville; Saskia Vennix (National Bank of Belgium, 2011)
This study assesses the economic importance of air transport and airport activities in Belgium in terms of employment, value added and investment over the period 2007 - 2009. The sector considered embraces not only the activities directly connected with air transport, but also all the activities which take place on site at the six Belgian airports (Antwerp, Brussels, Charleroi, Kortrijk, Liège, Ostend). The direct and indirect effects of the sector are estimated respectively on the basis of microeconomic data (mainly obtained from the Central Balance Sheet Office) and macroeconomic data (from the National Accounts Institute). The study also includes an analysis of the social balance sheet and certain ratios on the basis of Central Balance Sheet Office data. In 2009, the air transport sector thus defined generated over exteuro 6.1 billion in direct and indirect value added (or 1.8 % of Belgium's GDP), and provided direct or indirect employment for 80,300 people in full-time equivalents (or 2 % of domestic employment in FTE). Brussels Airport was the one most affected by the decline in global traffic in 2009, as a result of the economic crisis: in that year it ceased to be Belgium's principal cargo airport, ceding that position to Liège Airport. However, the national airport still ranks first in the passenger market, accounting for almost three-quarters of traffic in 2010, despite the exponential growth of traffic at Charleroi Airport. Together, these two airports represented almost 97 % of passenger traffic passing through Belgium in 2010.
Keywords: C67; D40; J21; L93; R15; R34; R41; 330; Air transport; airport activities; sector analysis; indirect effects; employment; value added; investments; Luftfahrtindustrie; Flughafen; Flughafenmanagement; Branchenentwicklung; Verkehrsstatistik; Belgien